আজব ও জবর-আজব অর্থনীতি - খান, আকবর আলি 1944- (ঢাকা : প্রথমা প্রকাশন, 2013)
Articles on economic conditions of Bangladesh.
Includes bibliographical references and index.
AAL
Development Book Agency (DBA)
In Bengali.
Keywords: Bangladesh -- Economic policy